Evolução histórica da tributação no Brasil e algumas sugestões para a reforma tributaria - Ferreira, Luiz Carlos (2012)
This dissertation on the story of taxes involves the Ancient Period, the Middle Ages, the Modern Ages and the beginning of the Contemporary Ages. We have also written about the collection system during the Empire, the arrival of the Royal Family in Brazil and their departure. The documentary research is based on the main federal taxes: Income Tax on Companies (IRPJ*), Import Duty (I I*), Financial Transactions Tax (IOF*), Manufactured Goods Tax (IPI*), Social Integration Program (PIS*), and Contribution for Social Security Finance (COFINS*). We have researched the period of sixty years, starting from the 50 th decade till the first decade of 2000. We have also researched the government revenues and expenses, as well as the government net revenue, year per year, and the taxation in the said period. From the 50 th to the 90 th decades we have presented the governments troubles and their stories, the main events, the change of currency in the period and the analysis of the revenues per year. We reached the 2000 year, and completed our survey with the main government taxes and expenses . We have completed our thesis with an analysis of the Brazilian Tax System, and we have also analysed the companies classified as National Simple ones, from 2000 up to 2010. We have mentioned the advantages of being a National Simple company, and the limits of the companies: Micro (ME*), Small (EPP*), Medium and Big companies. This survey finished with the last census made in Brazil in 2010, and we defined as a final conclusion and suggestion , which is the best Tax System for Brazil nowadays